An extended model of school-university partnership for professional development: bridging universities' theoretical knowledge and teachers' practical knowledge. Issue 2 (15th March 2023) - Mohamad Nasri, Nurfaradilla; Nasri, Nurfarahin; Abd Talib, Mohamad Asyraf
ABSTRACT: The United Nations Sustainable Development Goal (SDG) 4: Quality Education has recently driven more outreach teacher professional development (PD) programmes. While research evidence shows the importance of school-university partnerships for effective PD programmes, this research area remains under-investigated in many developing countries, including Malaysia. This qualitative study investigated the experiences and perspectives of 40 primary school teachers who participated in a three-phase, school-university PD programme. Phase 1 emphasised reflective pedagogy and co-development of teaching interventions. Phase 2 focused on classroom teaching intervention and continuous feedback on teaching methods, whereas Phase 3 consisted of interview sessions. Guided by the 'Interconnected Model of Teacher Professional Growth', an extended version of the model was developed to include an emerging domain; the Initial Positive Perception Domain. This domain addresses teachers' voluntary involvement and their clear intention to collaborate with the university researchers. Most importantly, this domain facilitates positive interaction between the existing domains in the model by promoting teachers' reflective pedagogical practice and strengthening the collective learning community. This study provides explicit evidence that a teacher's initial positive perception towards school-university partnership serves as a fundamental bridge between theoretical k nowledge and practical knowledge for developing highly effective PD programmes.